BIOFILIA DAN NEKROFILIA: ANALISIS SOSIOLOGI SASTRA NOVEL LA BÊTE HUMAINE KARYA EMILE ZOLA - Shahab, Ali (Jurnal Kawistara, 2011)
Using the genetic structural analysis suggested by Lucien Goldmann, it has been shown that EmileZola, an adherent of naturalism, has managed to expose a distinctive world view through the mediationof his work bring La bête humaine. Through his career as an author who fully engaged in the social andpolitical life of his time, Zola firmly demonstrated a world view different than contemporary rulers. Hisinvolvement in the political field, his support and empathy for the weak who became victims of an unjustcapitalist system, and his commitment to the truth in which he believed, produced changes in the socialand political fields. This is evident from the contemporary recognition of social rights of workers and therelease of Alfred Dreyfus from prison. Yet for all that he paid with his life; Zola was assassinated bypolitical opponents.